SIDC & FBM collaborated to organize INVESTED program - UiTM, Faculty of Business and Management (UiTM, 2023)
On 28 Nov 2023, the INVESTED program under SIDC collaborated with the Faculty of Business and Management UiTM Puncak Alam and several key people in the industry, such as YM Tengku Zarina Tengku Chik, the Chief Executive Officer of Security Industry Development Corporation (SIDC), Tan Sri Azman Haji Mokhtar, Chairman of Lembaga Tabung Haji Malaysia, and Dato' Zain Azhari Mazlan, the Executive Director of Corporate Finance and Investments of Securities Commission Malaysia. Also part of the collaboration were Tracy Chen Wee Keng, the CEO of Am Investment Bank Berhad, Intan Ruhanida Ramli, Head of InvestED Secretariat, Security Commission Malaysia, Kelvin Ho Jern Yang, Head of Futures, Affin Hwang Investment Bank Berhad, Shahrin Shaikh Mohd, Chief Compliance, Risk and Legal Officer, AHAM Asset Management Berhad, and a moderator, Nadia Azmi, a TV3 News Anchor.